Nanodiamond–Quantum Sensors Reveal Temperature Variation Associated to Hippocampal Neurons Firing. Issue 28 (25th July 2022) - Petrini, Giulia; Tomagra, Giulia; Bernardi, Ettore; Moreva, Ekaterina; Traina, Paolo; Marcantoni, Andrea; Picollo, Federico; Kvaková, Klaudia; Cígler, Petr; Degiovanni, Ivo Pietro; Carabelli, Valentina; Genovese, Marco
Abstract: Temperature is one of the most relevant parameters for the regulation of intracellular processes. Measuring localized subcellular temperature gradients is fundamental for a deeper understanding of cell function, such as the genesis of action potentials, and cell metabolism. Notwithstanding several proposed techniques, at the moment detection of temperature fluctuations at the subcellular level still represents an ongoing challenge. Here, for the first time, temperature variations (1 °C) associated with potentiation and inhibition of neuronal firing is detected, by exploiting a nanoscale thermometer based on optically detected magnetic resonance in nanodiamonds. The results demonstrate that nitrogen‐vacancy centers in nanodiamonds provide a tool for assessing various levels of neuronal spiking activity, since they are suitable for monitoring different temperature variations, respectively, associated with the spontaneous firing of hippocampal neurons, the disinhibition of GABAergic transmission and the silencing of the network. Conjugated with the high sensitivity of this technique (in perspective sensitive to < 0.1 °C variations), nanodiamonds pave the way to a systematic study of the generation of localized temperature gradients under physiological and pathological conditions. Furthermore, they prompt further studies explaining in detail the physiological mechanism originating this effect. Abstract : Measuring subcellular temperature gradients is fundamental for a deeper understanding of cell function. Here, for the first time, by exploiting a nanoscale thermometer based on optically detected magnetic resonance in nanodiamonds, 1 K temperature variations, associated with neuronal firing potentiation/silencing, are detected. This result in perspective will provide a tool for assessing neuronal spiking activity under physiological and pathological conditions.